The Effect of Diet Patterns, Food Security and Clean and Healthy Living Behavior (PHBS) on the Incidence of Stunting In Lontar Village, Tirtayasa District, Serang Regency In 2024 - Ajeng Mahatur; Fajar Saputra (Sean Institute, 2025)
Stunting is a condition where a toddler has a height that is lower than it should be according to age. Diet, Clean and Healthy Living Behavior (PHBS) and Food Security are some of the factors that play a major role in stunting. The purpose of this study was to determine the direct and indirect effects of the relationship between Diet, Clean and Healthy Living Behavior and Food Security on Stunting Incidence. The research design was carried out with a case study to determine the effect of diet, food security and clean and healthy living behavior on the incidence of toddler Stunting in Lontar Village, Tirtayasa District, Serang Regency in 2024. The population of this study were toddlers aged 2-5 years who had their height measured in January - August 2024 totaling 3,598 toddlers. Consisting of a case population, namely toddlers with Stunting as many as 229 toddlers. The results of the study on the indirect effect of PHBS (X2) on Stunting Incidence (Y), through Food Security (Z) were 0.015. P-Values = 0.341 > 0.05, it is concluded that Food Security (Z) does not significantly mediate the relationship between PHBS (X2) and Stunting Incidence (Y), and the indirect effect of Dietary Patterns (X1) on Stunting Incidence (Y), through Food Security (Z) is 0.127. P-Values = 0.035 <0.05, it is concluded that Food Security (Z) significantly mediates the relationship between Dietary Patterns (X1) and Stunting Incidence (Y). Dietary Patterns, PHBS and Food Security have a very significant influence on stunting incidence in Lontar Village, Tirtayasa District, Serang Regency. Of the three direct variables, the Dietary Pattern variable is the one with the largest value that greatly influences stunting incidence, which is 49.4%. While the two indirect variables for the mediation relationship of Food Security do not significantly affect the relationship between PHBS and Stunting Incidence, Food Security has an effect and significantly mediates the relationship between Dietary Patterns and Stunting Incidence.